Molecular dynamics simulations of ultrathin water film confined between flat diamond plates - Khomenko, A.V.; Prodanov, N.V. (Condensed Matter Physics, 2008)
Molecular dynamics simulations of ultrathin water film confined between atomically flat rigid diamond plates are described. Films with thickness of one and two molecular diameters are concerned and TIP4P model is used for water molecules. Dynamical and equilibrium characteristics of the system for different values of the external load and shear force are investigated. An increase of the external load causes the transition of the film to a solidlike state. This is manifested in a decrease of the diffusion constant and in the ordering of the liquid molecules into quasidiscrete layers. For two-layer film under high loads, the molecules also become ordered parallel to the surfaces. Time dependencies of the friction force and the changes of its average value with the load are obtained. In general, the behaviour of the studied model is consistent with the experimental results obtained for simple liquids with spherical molecules. У роботi описано комп’ютерне моделювання методом молекулярної динамiки ультратонкого шару води, стиснутого мiж атомарно-плоскими жорсткими алмазними поверхнями. Розглянуто плiвки товщиною один i два молекулярних дiаметри, для молекул води використано модель TIP4P. Вивчено динамiчнi й рiвноважнi характеристики системи для рiзних значень зовнiшнього навантаження i зсувної сили. Збiльшення зовнiшнього тиску обумовлює перехiд плiвки до твердоподiбного стану. Це виявляється у зменшеннi коефiцiєнту дифузiї й утвореннi молекулами рiдини квазiдискретних шарiв. У плiвцi товщиною два молекулярних дiаметри за високих навантажень молекули також упорядковуються паралельно до поверхонь. Отримано часовi залежностi сили тертя i змiни її середнього значення iз навантаженням. У цiлому, поведiнка моделi, що розглядається, узгоджується iз експериментами для простих рiдин, молекули яких мають сферичну форму.